A Hydronium Solvate Ionic Liquid: Facile Synthesis of Air-Stable Ionic Liquid with Strong Brønsted Acidity. Issue 3 (1st January 2018) - Kitada, Atsushi; Takeoka, Shun; Kintsu, Kohei; Fukami, Kazuhiro; Saimura, Masayuki; Nagata, Takashi; Katahira, Masato; Murase, Kuniaki
Abstract : A new kind of ionic liquid (IL) with strong Brønsted acidity, i.e., a hydronium (H3 O + ) solvate ionic liquid, is reported. The IL can be described as [H3 O + ·18C6]Tf2 N, where water exists as the H3 O + ion solvated by 18-crown-6-ether (18C6), of which the counter anion is bis(trifluoromethylsulfonyl)amide (Tf2 N − ; Tf = CF3 SO2 ). The hydrophobic Tf2 N − anion makes [H3 O + ·18C6]Tf2 N stable in air. The Hammett acidity function ( H 0 = −4.4) of molten [H3 O + ·18C6]Tf2 N, evaluated using the indicator method, is a new record for ILs and indicates strong aciditiy. The findings regarding this proton-condensed solvate IL are of fundamental interest, and will help in the design of media for new acid-base reactions.